Trading Forward in the Brazilian Electricity Market - Coutinho, Paulo Cesar; Oliveira, Andre Rossi de (International Journal of Energy Economics and Policy, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> We study the interaction between forward and spot electricity markets in a scenario where buyers and sellers are price takers in the forward market and trade through marketers, who play a Cournot game. Our model’s main features come from the Brazilian electricity market, where a free contract market coexists with a regulated contract market, and the spot price is the output of a stochastic dynamic algorithm. We are able to show that the price of energy bought (sold) forward decreases (increases) with the number of marketers, and that, as a result, full hedging is achieved in the limit. We also investigate the effects on prices of changes in the number of market participants and in aggregate consumption and supply, an exercise that yields important policy recommendations for the Brazilian regulator. Keywords: Forward and spot markets; marketers; Brazilian electricity market; Cournot; hedging. JEL Classifications: C61; C72; G10; L13; L94 <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->